Values of Islamic Economic System in Ritual "Mappadendang" - Abdul Rahim (Al-Ulum, 2016)
Cultural diversity that exists in Indonesia is one potential that must be developed and preserved throughout the cultures as long as they not incompatible with the moral values of Islam. In fact, this diversity provides vibrant colors varying as a tradition that characterizes respective tribes and ethnics. In the culture of the Bugis, one of the cultural or ritual that is routinely performed each year in agricultural activities (harvest) is mappadendang, attended by all farmers. This ritual is performed as a form of joy and gratitude on the Creator, for abundant agricultural crops. In addition to the form of joy, the mappadendang ritual also intended to preserve the cultural heritage of their ancestors. Mappadendang in Pinrang itself coins philosophical and religious values which are very high and are a means to strengthening the unity and integrity. The importance of cooperation within the traditional mappadendang ritual includes carrying values of the Islamic economic system, such as, to work earnestly for seeking halal earnings, to form solid society with solid social order, justice, income distribution, eradicating the monopoly, individual freedom in order to obtain social welfare.